Tragia plukenetii Radcl.-Sm. (Euphorbiaceae): An Addition to Flora of Allahabad, Uttar Pradesh - Singh, Renu; Narain, Satya; Fatima, Nahid (Current Botany, 2020)
Tragia plukenetii Radcl.-Sm. is reported as a new addition to the Flora of Allahabad district of Uttar Pradesh. A detailed description, up to date nomenclature and photographs are provided here to facilitate its easy and correct identification in the field.